Smart Irrigation and Fertigation - Mohd Jefry, Mohamad Hariz Bin; Mohamed Nor, Mohd Faizal; Ajis, Adriel; Ab Rahman, Muhammad Haziq Syazwan (Multidisciplinary Applied Research and Innovation, 2022)
Intelligent irrigation system for fertigation system for the farmer is a project that aims to improve a new modern life are experiencing various problems, especially inconsistent crop production and the very high cost of fertilizers and pesticides. This project to study about the fertigation system used in the agricultural sector in Malaysia and build an intelligent irrigation system simulation system for a fertigation system. Next, this project is to study the irrigation system used by modern farmers in Malaysia. To build a smart irrigation system based on the Arduino uno micro controller. Irrigation systems are used for agricultural crops based on leafy vegetables on a small scale. For this project we use a component from proteus which is arduino uno, LED, resistor , ultrasonic sensor and we also using blynk. Next, this system can be started if the timer is on and the valve solenoid will open and water can flow to the plant. The primary goal of this initiative is to help facilitate modern farmers in the fertilization process.